2019
DOI: 10.1111/hel.12659
|View full text |Cite
|
Sign up to set email alerts
|

Twice‐a‐day PPI, tetracycline, metronidazole quadruple therapy with Pylera® or Lactobacillus reuteri for treatment naïve or for retreatment of Helicobacter pylori. Two randomized pilot studies

Abstract: Background Bismuth is no longer available in Europe except as part of combination therapy. Lactobacillus reuteri has also been used as an adjuvant for Helicobacter pylori therapy. We aimed to investigate the efficacy of a b.i.d. quadruple therapy containing Pylera® or L reuteri for H pylori infection. Materials and Methods We performed two open‐label randomized pilot studies. Adult patients positive for H pylori were randomly assigned to b.i.d therapy with quadruple therapy containing bismuth (2 capsules of Py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…Bismuth intake may lead to abdominal discomfort by decreasing peristalsis and bowel frequency, because it shows antidiarrheal effects by decreasing the fluid and electrolytes flowing into the intestines . A comparison study between the bismuth‐containing quadruple therapy and Lactobacilli reuteri ‐containing quadruple therapy suggested replacement of bismuth with probiotics; however, patient compliance, efficacy, and drug safety were not different between the two groups …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bismuth intake may lead to abdominal discomfort by decreasing peristalsis and bowel frequency, because it shows antidiarrheal effects by decreasing the fluid and electrolytes flowing into the intestines . A comparison study between the bismuth‐containing quadruple therapy and Lactobacilli reuteri ‐containing quadruple therapy suggested replacement of bismuth with probiotics; however, patient compliance, efficacy, and drug safety were not different between the two groups …”
Section: Discussionmentioning
confidence: 99%
“…21 A comparison study between the bismuth-containing quadruple therapy and Lactobacilli reuteri-containing quadruple therapy suggested replacement of bismuth with probiotics; however, patient compliance, efficacy, and drug safety were not different between the two groups. 22 There are limitations to this study. First, this is not a prospective study.…”
Section: Ta B L Ementioning
confidence: 90%
“…The eradication rate was 100% in the bismuth-containing regimen against 90% in the probiotic group. The authors concluded that Gastrus ® might be considered when using bismuth is contraindicated or unavailable [ 37 ].…”
Section: Use Of L Reuteri 17938 (Or Mother Strain Atcc 55730) Against Hp Infection Without Antibioticsmentioning
confidence: 99%
“…Moreover, L. Reuteri produces antimicrobial molecules and promotes the development and the functionality of regulatory T cells, strengthening the gut barrier, and decreasing the microbial translocation from the intestinal lumen to the tissue, as reported by studies conducted on animal models [ 7 ], on humans [ 8 ] and in vitro [ 9 ]. Literature preclinical studies [ 10 ], using genetic tools such as genome sequencing, molecular tools, and genomic-based approaches (both in mice and then in humans) showed that L. reuteri has multiple beneficial effects on gastrointestinal symptoms, on gut infections, HP eradication, antibiotic-associated diarrhea, inflammatory bowel syndrome (IBS), inflammatory bowel disease (IBD), and colorectal cancer [ 11 , 12 , 13 ]. It can reduce abdominal pain in infantile colic, the functional abdominal discomfort in children, and it can decrease crying due to necrotizing enterocolitis in preterm neonates [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%